A decellularized flowable placental connective tissue matrix supports cellular functions of human tenocytes in vitro - Yong Mao; Nikita John; Nicole M. Protzman; Adam Kuehn; Desiree Long; Raja Sivalenka; Radoslaw A. Junka; Anna Gosiewska; Robert J. Hariri; Stephen A. Brigido (Journal of Experimental Orthopaedics)
Abstract Purpose Injectable connective tissue matrices (CTMs) may promote tendon healing, given their minimally invasive properties, structural and biochemical extracellular matrix components, and capacity to fill irregular spaces. The purpose of this study is to evaluate the effects of placental CTMs on the cellular activities of human tenocytes. Decellularization, the removal of cells, cell fragments, and DNA from CTMs, has been shown to reduce the host’s inflammatory response. Therefore, the authors hypothesize that a decellularized CTM will provide a more cell‐friendly matrix to support tenocyte functions. Methods Three human placental CTMs were selected for comparison: AmnioFill® (A‐CTM), a minimally manipulated, non‐viable cellular particulate, BioRenew™ (B‐CTM), a liquid matrix, and Interfyl® (I‐CTM), a decellularized flowable particulate. Adhesion and proliferation were evaluated using cell viability assays and tenocyte migration using a transwell migration assay. Gene expression of tenocyte markers, cytokines, growth factors, and matrix metalloprotease (MMP) in tenocytes were assessed using quantitative polymerase chain reaction. Results Although A‐CTM supported more tenocyte adhesion, I‐CTM promoted significantly more tenocyte proliferation compared with A‐CTM and B‐CTM. Unlike A‐CTM, tenocyte migration was higher in I‐CTM than the control. The presence of I‐CTM also prevented the loss of tenocyte phenotype, attenuated the expression of pro‐inflammatory cytokines, growth factors, and MMP, and promoted the expression of antifibrotic growth factor, TGFβ3. Conclusion Compared with A‐CTM and B‐CTM, I‐CTM interacted more favorably with human tenocytes in vitro. I‐CTM supported tenocyte proliferation with reduced de‐differentiation and attenuation of the inflammatory response, suggesting that I‐CTM may support tendon healing and regeneration in vivo.